Harms from other people's drinking: an international survey of their occurrence, impacts on feeling safe and legislation relating to their control. Issue 12 (23rd December 2015) - Bellis, Mark A; Quigg, Zara; Hughes, Karen; Ashton, Kathryn; Ferris, Jason; Winstock, Adam
Abstract : Objective: To examine factors associated with suffering harm from another person's alcohol consumption and explore how suffering such harms relate to feelings of safety in nightlife. Design: Cross-sectional opportunistic survey (Global Drug Survey) using an online anonymous questionnaire in 11 languages promoted through newspapers, magazines and social media. Subjects: Individuals (participating November 2014–January 2015) aged 18–34 years, reporting alcohol consumption in the past 12 months and resident in a country providing ≥250 respondents (n=21 countries; 63 725 respondents). Main outcome measures: Harms suffered due to others' drinking in the past 12 months, feelings of safety on nights out (on the way out, in bars/pubs, in nightclubs and when travelling home) and knowledge of over-serving laws and their implementation. Results: In the past 12 months, >40% of respondents suffered at least one aggressive (physical, verbal or sexual assault) harm and 59.5% any harm caused by someone drunk. Suffering each category of harm was higher in younger respondents and those with more harmful alcohol consumption patterns. Men were more likely than women to have suffered physical assault (9.2% vs 4.7; p<0.001), with women much more likely to suffer sexual assault or harassment (15.3% vs 2.5%; p<0.001). Women were more likely to feel unsafe in all nightlife settings, with 40.8% typically feeling unsafe on the way home. In all settings, feeling unsafe increased with experiencing more categories of aggressive harm by a drunk person. Only 25.7% of respondents resident in countries with restrictions on selling alcohol to drunks knew about such laws and 75.8% believed that drunks usually get served alcohol. Conclusions: Harms from others' drinking are a threat to people's health and well-being. Public health bodies must ensure that such harms are reflected in measures of the societal costs of alcohol, and must advocate for the enforcement of legislation designed to reduce such harms.